PENGARUH LAMA PERENDAMAN TERHADAP PELEPASAN ION NIKEL DAN KROMIUM KAWAT AUSTRALIA TIPE REGULAR, SPESIAL, SERTA PREMIUM DALAM SALIVA BUATAN pH NORMAL - , Agus Suprapto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Australian wire was used in fixed orthodontic treatment with Begg technique as arch wire.This wire was basically a stainless steel had several grade: regular, special and premium. Immersion of stainless steel in artificial saliva was trigger to release of metal ion. The purpose of this study was to observe the difference of ionic nickel and chromium released between the length of immersion period and the wire grade after immersion in artificial saliva of normal pH. Thirty pieces of Australian wire with regular, special, and premium grades were used in this study, with each piece of wire had 0,130 gram of weight. Wire immersion in artificial saliva with normal pH was carried out for 1, 7, 14, 28, 35, and 42 days. The nickel and chromium ion release were measured using Atomic Absorption Spectrophotometry. The Data of measurements were analyzed using Kruskal-Wallis test. The result showed a significant difference of nickel ion release were in days of 28, 35 and 42 immersion time, Australian wire grades and interaction immersion time with Australian wire grades. Chromium ion released could not be observed until the 42nd day of immersion. Conclusion: Nickel ion release of Australian wire were different in days of 28, 35 and 42 immersion time, Australian wire grades, and interaction immersion time with Australian wire grades. The ionic nickel was highly released from the special grade Australian wire compared with regular and premium grades on every immersion period. Chromium ion released could not be observed until the 42nd day of immersion.